Interannual Relationship between ENSO and Atlantic Storm Track in Spring Modulated by the Atlantic Multidecadal Oscillation - Chenfei Liao; Haiming Xu; Jiechun Deng; Leying Zhang (Atmosphere, 2018)
It has been well documented that storm track activity are closely related to the weather and short-term climate variability in the extratropics, which is affected by sea surface temperature anomalies over the tropical eastern Pacific Ocean. Interannual relationship between the El Niño-Southern Oscillation (ENSO) and the Atlantic storm track (AST) in spring modulated by the Atlantic multidecadal oscillation (AMO) was investigated using reanalysis data and model simulations in this study. The meridional displacement of the AST is significantly correlated with ENSO during negative AMO phase, while no significant relationship is found during positive AMO phase. This may be due to the difference of 500-hPa geopotential height anomalies induced by ENSO in different AMO phases. For an El Niño event during the negative AMO phase, an anomalous 500-hPa wave train propagates eastward across the North American continent, with positive height anomalies at the high latitudes, extending from South Canada to Newfoundland. Thus, easterly wind anomalies appear over central North America, upstream of the negative AST anomaly. Accordingly, the local eddy growth rate (EGR) and baroclinic energy conversion (BC) are obviously reduced, which weaken (strengthen) the southern (northern) part of the climatological AST. As a result, the AST is shifted northward significantly. During the positive AMO phase, the ENSO-related anomalous wave train at 500 hPa only propagates northeastward and is largely suppressed over Northwest Canada, with positive height anomalies confined to the northwest of North America. Therefore, no significant changes of the westerly jet, EGR and BC are found in the upstream region of the AST, and the meridional location of the AST generally remains unchanged. Most previous studies investigate AST variabilities in winter, and few focus on AST in spring. This work may be helpful in understanding more about the interannual and interdecadal variations of springtime AST and in further studying the weather and short-term ...